Analisis Penggunaan Gimkit Sebagai Media Pembelajaran Dalam Meningkatkan Keterlibatan Siswa - Hanifah, Maryam; Hafidz, Hafidz (Journal of Comprehensive Science, 2025)
Sustaining and enhancing student engagement in the educational process is a critical issue in contemporary pedagogy. Amidst rapid digital technological advancements, various innovative platforms are emerging as instructional tools, one of which is Gimkit. This research aims to examine the implementation of Gimkit as a learning medium and its influence on increasing active student participation. By employing both qualitative and quantitative approaches, this study explores several dimensions, including the availability of interactive learning content, the dynamics of student interaction and involvement, accessibility and ease of use, pedagogical effectiveness, learning support, performance evaluation, as well as challenges and feedback from learners. The analysis findings indicate that Gimkit positively contributes to student engagement in the learning process. The variety of game modes and interactive features available have successfully stimulated student interest and participation, reflected in the high level of enthusiasm during each learning session integrating Gimkit. Student feedback suggests significant appreciation for the utilization of Gimkit as a teaching medium, although some improvement recommendations were identified to optimize the holistic learning experience. The implications of this study are expected to provide guidance for educational institutions in adopting Gimkit to enhance the quality and effectiveness of student learning.